Phagocytic cell responses to silica-coated dithiocarbamate-functionalized iron oxide nanoparticles and mercury co-exposures in Anguilla anguilla L. - Costa, Leonor
Immune system responses in fish are considered as suitable and sensitive biomarkers for monitoring aquatic pollution. However, a clear knowledge gap persists in the literture on the immunotoxic potential of engineered nanoparticles toward aquatic organisms such as fish. Employing major enzymatic- (glutathione reductase, GR; glutathione peroxidase, GPX; glutathione sulfo-transferase, GST; catalase, CAT) and thiol- (non-protein thiols, NP-SH; total glutathione, TGSH)-based defense biomarkers, this study assessed the response of phagocytes isolated from peritoneum (P-phagocytes), gill (G-phagocytes), head kidney (HK-phagocytes), and spleen (S-phagocytes) of European eel (Anguilla anguilla L.) to silica-coated magnetite particles (Fe3O4@SiO2/SiDTC, hereafter called IONP; size range: 82 +/- 21 to 100 +/- 30 nm; 2.5 mg L-1) alone and IONP and mercury (Hg; 50 mu g L-1) concomitant exposures. Responses of previous biomarkers were studied in P-phagocytes, G-phagocytes, HK-phagocytes, and S-phagocytes collected during 0, 2, 4, 8, 16, 24, 48, and 72 h of exposures. Contingent to hour of exposure to IONP, Hg, and IONP + Hg GST, GPX, CAT, NP-SH, and TGSH exhibited their differential responses in all the phagocytic cells considered. In particular, under IONP exposure, the potential occurrence of the GSH-independent antioxidant defense was indicated by the observed herein inhibition in the enzymatic- and thiol-based defense in A. anguilla phagocytes. In contrast, the response of P-, G-, HK-, and S-phagocytes to the increasing Hg exposure period reflected an increased detoxification activity. Notably, the occurrence of an antagonism between IONP and Hg was depicted during late hours (72 h) under IONP + Hg concomitant exposure, where elevations in the defense biomarkers were depicted. Overall, the P-, G-, HK-, and S-phagocytic cells exhibited a differential induction in the studied enzymes and thiols to counteract impacts of IONP, Hg, and IONP + Hg concomitant exposures. Future studies on the fish immunotoxicity responses to IONP exposure in multi-pollution conditions can be benefited with the major outcomes of the present study.